2015
DOI: 10.3389/fpls.2015.00074
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the serine acetyltransferase gene family of Vitis vinifera uncovers differences in regulation of OAS synthesis in woody plants

Abstract: In higher plants cysteine biosynthesis is catalyzed by O-acetylserine(thiol)lyase (OASTL) and represents the last step of the assimilatory sulfate reduction pathway. It is mainly regulated by provision of O-acetylserine (OAS), the nitrogen/carbon containing backbone for fixation of reduced sulfur. OAS is synthesized by Serine acetyltransferase (SERAT), which reversibly interacts with OASTL in the cysteine synthase complex (CSC). In this study we identify and characterize the SERAT gene family of the crop plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 87 publications
(136 reference statements)
3
20
0
Order By: Relevance
“…The total extractable SERAT and OASTL activities were measured in order to test if the changed cysteine contents in leaves and roots were due to drought-induced changes in enzyme activities. As observed for other plant species, total OAS-TL activity was about 50–500 times higher than SERAT activities [24, 3336], stating that the latter catalyzes the rate-limiting reaction also in maize (Fig. 4a-d).…”
Section: Resultssupporting
confidence: 70%
“…The total extractable SERAT and OASTL activities were measured in order to test if the changed cysteine contents in leaves and roots were due to drought-induced changes in enzyme activities. As observed for other plant species, total OAS-TL activity was about 50–500 times higher than SERAT activities [24, 3336], stating that the latter catalyzes the rate-limiting reaction also in maize (Fig. 4a-d).…”
Section: Resultssupporting
confidence: 70%
“…4 ). A recent study in Vitis vinifera showed no changes of OAS concentration between WW and droughted plants, while it showed altered expression of serine acetyltransferases genes ( VvSERAT1;2 up-regulated; VvSERAT3;1 down-regulated) that convert serine to OAS (Tavares et al 2015 ). OAS is then converted to cysteine, which is the precursor of glutathione (GSH), a major antioxidant, for which accumulation under drought, cold and heat shock has been well documented (Nieto-Sotelo and Ho 1986 ; Dhindsa 1991 ; Kocsy et al 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…APS is then enzymatically converted to sulphite by APS reductase and sulphite to sulphide by the ferredoxin-dependent enzyme; sulphite reductase. The combination of sulphite with the carbon skeleton derived from serine (Ser) through O-acetylserine (OAS) synthesis under the influence of Ser acetyltransferase then yields cysteine (Saito, 2000 ; Tavares et al ., 2015 ).…”
Section: Discussionmentioning
confidence: 99%